Newspaper Coverage of Sexual Assaults in South Korea: Before and after #MeToo Movement (Proceedings of the International Conference on Future of Women, 2020)
This study explores differences in South Korean newspaper coverage related to cases ofsexual assault on females before and after the #MeToo movement. To this end, a content analysiswas conducted to examine the framing of newspaper coverage of sexual assault by politicians in2014 and 2018. In total, 755 news stories were analysed, revealing 10 times increase in the numberof articles dealing with sexual violence cases after the #MeToo movement. In addition, it was foundthat the number of newspaper articles representing the voices of women who were victims of sexualassault or representing the position of women's organizations calling for social change and theprotection of women's rights increased significantly after the #MeToo movement. In particular, asignificant increase in newspaper coverage discussing problems with the legal system and calling foran urgent improvement to its dealings with sexual assault cases was found. Despite the #MeToomovement, however, the examined newspaper coverage still used an episodic frame more often thana thematic one in dealing with sexual violence against women and the articles still contained manyprovocative words, such as ‘adultery’ and ‘infidelity’, aimed at arousing readers' curiosity andinterest.
Keywords: Sexual assault; framing analysis; Newspaper coverage; #MeToo